Purification of RIP60 and RIP100, mammalian proteins with origin-specific DNA-binding and ATP-dependent DNA helicase activities. - Dailey, L (1990)
Replication of the Chinese hamster dihydrofolate reductase gene (dhfr) initiates near a fragment of stably bent DNA that binds multiple cellular factors. Investigation of protein interactions with the dhfr bent DNA sequences revealed a novel nuclear protein that also binds to domain B of the yeast origin of replication, the autonomously replicating sequence ARS1. The origin-specific DNA-binding activity was purified 9,000-fold from HeLa cell nuclear extract in five chromatographic steps. Protein-DNA cross-linking experiments showed that a 60-kDa polypeptide, which we call RIP60, contained the origin-specific DNA-binding activity. Oligonucleotide displacement assays showed that highly purified fractions of RIP60 also contained an ATP-dependent DNA helicase activity. Covalent radiolabeling with ATP indicated that the DNA helicase activity resided in a 100-kDa polypeptide, RIP100. The cofractionation of an ATP-dependent DNA helicase with an origin-specific DNA-binding activity suggests that RIP60 and RIP100 may be involved in initiation of chromosomal DNA synthesis in mammalian cells.